Jumpa Penggemar Artis dari Lensa Interaksi Parasosial Virtual - Puspita, Ratna; Nurwulan, Titis (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2024)
Meeting fans is something that is difficult to realize during the Covid-19 pandemic. However, the entertainment industry reproduces the relationship between fans and celebrities through social media-mediated fan encounters in order to balance the impact of business and intimate relationships with fans. Using a qualitative content analysis approach, the author explores celebrity and fan interactions at South Korean celebrity Lee Sung Kyung's fanmeeting via TikTok using Horton and parasocial theory. Previous research has not explained the interactions between celebrities and fans when fanmeetings take place in virtual spaces with a qualitative approach. The form of virtual fanmeetings actually repeats previous offline fanmeetings. Both sell artist personas as commodities. However, the absence of physical interaction makes these virtual fanmeetings very difficult to distinguish from broadcasts on conventional television. The author believes that fanmeetings are offline products that cannot be replaced with virtual content because they do not involve voluntary interactions such as hugs, handshakes, or other physical interactions that play a role in physical and emotional intimacy. This research strengthens Horton & Wohl's (11956) that the interaction between the audience and the celebrity is actually one-sided, not dialectical, controlled by the celebrity, and there is no mutual development of the relationship. Furthermore, celebrity parasocial interaction in this study is shown as